2019
DOI: 10.12737/stp-53201911
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of geomagnetic disturbances using the global survey method in real time

Abstract: A method for forecasting geomagnetic storms using the realization of the global survey method in real time is presented. The method is based on data from the worldwide network of neutron monitors NMDB. Using this method, we analyze the behavior of components of three-dimensional angular distribution of cosmic rays in the interplanetary medium, which were due to the first two spherical harmonics, over the period from 2013 to 2018. We have established that the main parameters that respond to the arrival of geoef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…As shown by our studies, the main predictors in CR that actively respond to geoeffective disturbances of the interplanetary medium approaching Earth are changes in amplitudes of zonal (north-south) components of the high-frequency part of the isotropic CR intensity (C 00) and the first two moments of the angular distribution (C 10 and C 20 ) [Grigoryev et al, 2017], which are included in the nine parameters determined by the global survey method [Krymsky et al, 1981] and may take both positive and negative values with respect to the ecliptic plane. The predictors may also be changes in the value and direction of the first harmonic vector and in the sum of amplitudes of zonal components, which occur before the interplanetary disturbance arrives in Earth's orbit.…”
Section: Experimental Data and Monitoring Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…As shown by our studies, the main predictors in CR that actively respond to geoeffective disturbances of the interplanetary medium approaching Earth are changes in amplitudes of zonal (north-south) components of the high-frequency part of the isotropic CR intensity (C 00) and the first two moments of the angular distribution (C 10 and C 20 ) [Grigoryev et al, 2017], which are included in the nine parameters determined by the global survey method [Krymsky et al, 1981] and may take both positive and negative values with respect to the ecliptic plane. The predictors may also be changes in the value and direction of the first harmonic vector and in the sum of amplitudes of zonal components, which occur before the interplanetary disturbance arrives in Earth's orbit.…”
Section: Experimental Data and Monitoring Methodsmentioning
confidence: 63%
“…The predictors may also be changes in the value and direction of the first harmonic vector and in the sum of amplitudes of zonal components, which occur before the interplanetary disturbance arrives in Earth's orbit. We can empirically determine the critical levels above which positive values of any of the three components or their sums most likely predict an abrupt decrease in the Dst index at the beginning of a geomagnetic storm [Grigoryev et al, 2019]. Yet, a significant decrease in negative values of these components or their sums below a certain critical value may indicate the most disturbed phase of the geomagnetic storm.…”
Section: Experimental Data and Monitoring Methodsmentioning
confidence: 99%
“…The creation of the NMDB network in 2007 served as an impetus for the implementation of the GSM method in real-time and in the study of the possibilities of the practical application of its results. The work carried out over the past 10 years in this direction (Grigoryev et al 2011a(Grigoryev et al , 2015(Grigoryev et al , 2017(Grigoryev et al , 2019Starodubtsev et al 2019) showed that it is possible to predict geomagnetic storms. As it turned out, the parameters of the angular distribution of CRs, identified using the GSM, actively respond to the approach of geoeffective disturbances of the interplanetary medium to the Earth.…”
Section: Forecasting Geomagnetic Stormsmentioning
confidence: 99%
“…Analysis of the results of the GSM for 2012-2018 made it possible to establish that anomalous changes in the magnitude and direction of the first harmonic vector (a 11 and b 11 ) and the amplitudes of the zonal (north-south) components (a 00 , a 10 and a 20 ) of the CR distribution can serve as predictors of geomagnetic disturbances. For the zonal components, the critical values of individual positive values or their sums were determined, the excess of which, with a probability of 75%, is a precursor of a sharp decrease of Dst-index at the beginning of the geomagnetic storm (Grigoryev et al 2019).…”
Section: Forecasting Geomagnetic Stormsmentioning
confidence: 99%
See 1 more Smart Citation